(3ebGdI aj GdJhMjOs - (3GHf YOj , jMji Hf YOj Hf MejO Hf RcQjG, CHh RcQjG,J (B364 (3g` s
(3ChdgG (B:s
(3GNJda GdbGFdhf HhMOGfjI GdNGdb JHGQc GSeg ai eYfi hMOGfjJg YeG jbhdg GdedC s
(3BNQgG (B:s
(3Ydi gPG GdEJbGf GdPi gi Ydjg HgPg GdGKGQ hMOgG abO JHjf EPG cejI YOO UaGJ GdHGQi Ld GSeg hYR PcQg adfNJJe gPg GdebGdI eY MeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdKGdK hGdYTQhfs
(3GfXQg eY GdeNWhW Qbe (B302 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHI QSGdI efTCI ai SfI (B328s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B211s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(23/4901) s
Keywords: (3GdJhMjO hGdedd hGdfMds